PHARMACOLOGICAL SCREENING OF ANTI-OBESITY POTENTIAL OF ACORUS CALAMUS LINN. IN HIGH FAT CAFETERIA DIET FED OBESE RATS - K, Athesh; G, Joshi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To study the anti-obesity potential of aqueous rhizome extract of Acoruscalamus Linn. (AREAC)in high fat diet fed obese rats. Methods: Adult strain male Wistar rats used in this study were fed with High Fat Diet (HFD) for 60 days. For the treatment groups,AREAC was administered in a dose levels of100, 200 and 300 mg/kgbw, orally once a day along with HFD. Rats fed with normal pellet chow were served as normal control. The effect of AREAC on physical parameterssuch as body weight, organ weight, fat pad weights and various biochemical parameterslike serum glucose, insulin, leptin,lipid profile, liver markers, kidney markers and oxidative stress markers were analysed.In-vitro pancreatic lipase inhibition assay of AREAC was also studied. Results: Data of in-vivo studies revealedsignificant (p<0.05) reduction in percentage body weight gain, organ weights, fat pad weights and levels of serum glucose, insulin and leptin after treatment with AREAC in a dose dependent manner. Also, administration of AREAC significantly inhibited the increases in the concentrations of triglycerides, total cholesterol, LDL-cholesterol, VLDL-cholesterol, free-fatty acid and phospholipids in a dose dependent manner whereas, the level of HDL-cholesterol was found to be elevated on treatment. Moreover, on treatment with test drug,the elevated levels of serum liver and kidney markerssuch as AST, ALT, ALP, urea, creatinine were also brought back to near normalcy. Antioxidant status was found to be enhanced in liver tissues after treatment.In-vitro studies showed significant inhibition in the activity of pancreatic lipaseby AREAC. Conclusion: The data of the results obtained clearly depicted that AREAC was found to have pronounced anti-obesity activity particularly at the dose levels of 300 mg/kg bw. KeyWords: Obesity, High Fat Diet, Leptin, AcoruscalamusLinn., Orlistat. Â Â